Comparative study on performance of flat plate and evacuated tube collectors solar water heater system - Hujailan, Faleh F.F.; Maleque, Md. Abdul; Rahman, Md. Mustafizur (2021)
In recent years, there is a tremendous demand for renewable energy for the sustainable energy usages in the buildings and other applications. This paper aims to study a comparative performance of flat plate and evacuated tube collectors solar water heating systems. The two types of solar water heater systems were designed and evaluated based on the requirements of the urban building dwellers. The F-chart method was used to study the performance efficiency of the solar water heater system at an operating temperature of 65 °C. An economic analysis was also carried out using the same tool for both types of collectors with the designed parameters. The performance efficiency results of flat plate and evacuated tube collector are 77 % and 67.3 %, respectively. The economic analysis of flat plate collector demonstrated a cost-effective design for the solar water heater system due to its steadiness and lower maintenance costs.